2018
DOI: 10.21070/jees.v3i1.1085
|View full text |Cite
|
Sign up to set email alerts
|

An ESP Needs Analysis: Addressing the Needs of English for Informatics Engineering

Abstract: English for specific purposes (ESP) have different needs of English language use. These needs will be the fundamental indicators to develop appropriate ESP syllabus. In order to find those needs, a need analysis research is necessary to conduct. This qualitative study addresses the result of ESP needs analysis for 95 Informatics Engineering of Muhammadiyah University of Ponorogo students. Brief reviews of ESP, needs analysis, and current learners’ situation of ESP classroom for Informatics Engineering are desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 14 publications
10
31
1
Order By: Relevance
“…Furthermore, for the long-term goal, the learners primarily express their intention to continue their study to higher education and to get a job. These findings correspond to the previous studies conducted by several scholars (Boroujeni & Fard, 2013;Liton, 2012;Nimasari, 2018;Poedjiastutie & Oliver, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, for the long-term goal, the learners primarily express their intention to continue their study to higher education and to get a job. These findings correspond to the previous studies conducted by several scholars (Boroujeni & Fard, 2013;Liton, 2012;Nimasari, 2018;Poedjiastutie & Oliver, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…This implies that they are basically unaware of the importance of the ESP materials related to their program. In contrast to those findings, an earlier study by Nimasari (2018) has revealed that the participants like to have topics that are relevant to their program, informatics engineering.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The objective of the research focuses on further examination of the previous research conducted specifically in the context of English for Informatics Engineering study program in Universitas Muhammadiyah Ponorogo. ESP syllabus for English for Informatics Engineering, its organized materials and tasks according to the research report studied by Nimasari (2018) Nimasari (2018 are presented in this research.…”
Section: Introductionmentioning
confidence: 99%